VIBRATIONAL FREQUENCY AND THERMODYNAMIC PROPERTIES OF NEUTRAL AND IONIC PYRENE AND ITS DERIVATIVES (FUDMA JOURNAL OF SCIENCES, 2023)
Thermodynamic properties of pyrene organic compound and its chlorinated derivatives in neutral and ionic state were investigated. Pyrene (C16H10) is an organic compound that possesses such properties which are essential in determining the future application of the molecule. The study is based on Density Functional Theory (DFT) using Becke’s three and Lee Yang Parr(B3LYP) functional with basis sets 6-311++G (d,p). These computations have been performed using Gaussian 03 software. Austin Model was also used to compute the heat of formation of the molecule and its derivatives in the two states at a temperature of 298K and 1 atm. Enthalpic stabilization is in the order of 2-chloropyrene > 1-chloropyrene > pyrene. IR spectrum shows insignificant difference among the molecules, the only noticeable difference is the charge status of the molecules; this is indeed what caused the significant variation in the IR spectrum distribution.
Keywords: Pyrene, thermodynamic, organic compound, DF, Gaussian 03, heat capacity, entropy, energy and Heat of Formation